ANALISIS PEMAHAMAN CYBERSECURITY DAN SISTEM OTOMASI TERHADAP KESIAPAN KERJA DI INDUSTRI OTOMASI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN VOKASIONAL MEKATRONIKA UNIVERSITAS NEGERI MAKASSAR - Apriliani, Astryd Dwi; Muh Ma’ruf Idris; Edy Sabara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the use of learning media in the learning process of Pancasila Education for tenth-grade senior high school students in Malang City and to determine students’ responses and participation toward the use of interactive PowerPoint (PPT) learning media. This study employed a qualitative approach with a descriptive research design. The research was conducted at SMA Laboratorium Universitas Negeri Malang involving tenth-grade students and a Pancasila Education teacher as research subjects. Data collection techniques included observation, documentation, questionnaires, and interviews. Data analysis used the Miles and Huberman model, consisting of data reduction, data presentation, and conclusion drawing. The results showed that the use of interactive PPT learning media had a positive impact on the Pancasila Education learning process. Students demonstrated positive responses because the learning media were considered attractive, easy to understand, and capable of increasing students’ focus and learning motivation. In addition, the use of interactive PPT media improved students’ participation in classroom activities, such as asking questions, answering questions, and engaging in classroom discussions. However, several obstacles were found, including excessive text in the PPT slides and technical problems with learning devices. Therefore, the development of more creative, interactive, and contextual learning media is needed to create a more effective and enjoyable learning process.